The CADI-study: Compression after device implantation - To examine the effect of a compressive dressing after device implantation or replacement focusing on the patient"s bleeding, hematomas and pain. (29th July 2021) - Fuglsbjerg, C; Philbert, BT; Risum, N; Vinther, M; Christensen, SW; Risom, SS
Abstract: Funding Acknowledgements: University Hospital Rigshospitalet, Centre for Cardiac, Vascular, Pulmonary and Infectious Diseases, Denmark Background: Bleeding and pocket hematomas are a known complication in pacemaker or implantable cardioverter defibrillator (ICD) implantations. Hematomas are associated with increased risk of infection and pain. Purpose: To investigate whether a compressive dressing applied for three hours can prevent bleeding, pocket hematomas and pain. Method: The study was a pseudo-randomized intervention study including patients scheduled for implantation or box change of a pacemaker or an ICD. In alternating months patients either received a compressive dressing (intervention group) or not (control group). Patients were excluded by the implanting physician if there was a clinical indication for a compressive dressing due to seeping bleeding. Patients were followed at the catheterization lab, for three hours at the ward and until the first outpatient control visit (1-3 months). The outcomes were: Bleeding, pocket hematomas and pain. The bleedings were graded as active bleeding or seeping bleeding or hematomas. Hematomas were measured by degree 1 to 3 (3 largest) and size (in cm). Pain was rated by the patient by numerical rank scale (NRS) from 0 to 10 (10 worst). Descriptive statistics were used. Results: A total of 191 patients were included, 95 patients in the intervention group. After inclusion 24 patients of the 96 patients in the control group were excluded by the implanting physician on clinical indication for a compressive dressing. Before the intervention there were significantly more patients with bleeding (graded as: Seeping bleeding) in the intervention group (n = 25, (26.9%)) compared to the control group (n = 4, (5.6%), p <0.001). No patients had developed pocket hematomas at the end of the procedure. Furthermore, the pain score was low in both groups (Total n = 19, NRS score ≤ 2.5). Over the next three hours in the ward, there was no significant difference in the bleeding (graded as: Seeping bleeding) in the groups (intervention: n = 8 vs. control: n = 3, p = 0.55). Two patients in each group had developed a pocket hematoma after three hours (p = 0.36) and the intervention group experienced more pain (intervention: 1.7 (±2.4) vs. control: 1.1(±1.7), p= 0.02). At the outpatient control 1-3 months after implantation, there was no significant difference between the groups related to bleeding, pocket hematomas and pain. Conclusion: Compressive dressing did not significantly reduce bleeding or the number of pocket hematomas after pacemaker or ICD implantation. In addition patients reported a slight increase in pain scores related to the compressive dressing. The results question routine compression after procedure, but should be validated in larger studies.